Astragalus and its formulas as a therapeutic option for fibrotic diseases: Pharmacology and mechanisms - Zhu, Yi; Chai, Yilu; Xiao, Guojin; Liu, Yufei; Xie, Xiaohong; Xiao, Wei; Zhou, Pengcheng; Ma, Wei; Zhang, Chuantao; Li, Liuying (Frontiers in Pharmacology, 2022)
Fibrosis is the abnormal deposition of extracellular matrix, characterized by accumulation of collagen and other extracellular matrix components, which will lead to organ dysfunction, morbidity, and even death. Despite the progress made in the understanding of the pathology and the clinical management of fibrosis, there are currently no therapies to prevent or reverse fibrosis, existing treatment options may lead to diarrhea, nausea, bleeding, anorexia and liver toxicity. Thus, it is urgent to find effective drugs for fibrotic diseases. Traditional Chinese medicine has played a vital role in fibrotic diseases, accumulating evidence has demonstrated that Astragalus can attenuate multiple fibrotic diseases, which include pulmonary fibrosis, cardiac fibrosis, liver fibrosis renal fibrosis and peritoneal fibrosis and so on, mechanisms may be related to inhibition of EMT, ROS, TGF-β1/Smads, apoptosis, inflammation pathways. In this review, we summarized the pharmacology and mechanisms of Astragalus in treating fibrotic diseases, the data reviewed demonstrates that Astragalus is a promising anti-fibrotic drug, its main anti-fibrotic components are Calycosin, Astragaloside IV, Astragalus polysaccharides and formononetin. We also review fomulas that contain Astragalus with anti-fibrotic effects, in which Astragalus and Salvia miltiorrhiza, Astragalus and Angelica Sinensis are the most commonly used combinations. We propose that combining active components into new formulations may be a promising way to develop new drugs for fibrosis. Besides, with further research, we believe the therapeutic effect of Astragalus on fibrosis will likely be clinically accepted and applied.